Genetic diversity in sorghum mini-core and elite rainy and post-rainy genotypes of India. Issue 2 (15th January 2016) - Ganapathy, Kuyyamudi Nanaiah; Rakshit, Sujay; Gomashe, Sunil Shriram; Audilakshmi, Suri; Hariprasanna, Krishna; Patil, Jagannath Vishnu
Abstract : Knowledge on genetic diversity is necessary to determine the relationships among the genotypes, which allow the selection of individual accessions for crop breeding programmes. The present study aimed at assessing the extent and pattern of genetic diversity within a set of 251 sorghum genotypes using SSR markers. A total of 393 alleles were detected from the 251 genotypes, with the number of alleles ranging from 2 (Xcup11) to 24 (Sb5-206) and an average of 10.07 alleles per primer pair. Pairwise Wright's FST statistic and Nei's genetic distance estimates revealed that the race and geographical origin were responsible for the pattern of diversity and structure in the genetic materials. In addition, the analysis also revealed high genetic differentiation between the rainy and post-rainy sorghum groups. Narrow diversity was observed among the different working groups in the rainy (restorers and varieties) and post-rainy (varieties and advanced breeding lines) sorghum groups. Neighbour-joining and STRUCTURE analysis also classified 44 elite lines broadly into two distinct groups (rainy and post-rainy). However, limited diversity within the rainy and post-rainy sorghum groups warranted an urgent need for the utilization of diverse germplasm accessions for broadening the genetic base of the Indian breeding programme. The diverse germplasm accessions identified from the mini-core accessions for utilization in breeding programmes are discussed.